EVALUATION OF MAXILLARY BONE DIMENSIONS IN SPECIFIC AREAS FOR REMOVABLE DENTURES - Dobromira Shopova; Tanya Bozhkova; Diyan Slavchev; Spas Muletarov; Zdravka Ivanova; Elena Bozhikov (Peytchinski Publishing, 2017)
Background: The removable prosthetics is a big part of Prosthetic Dentistry. The prosthetic field is very important for successful treatment with partial or complete dentures. Maxillary bone is covered with soft tissues, but its anatomy is essential for retention, chewing stability and comfort of the patients. Purpose: The study's aim was to evaluate the dimensions of maxillary bone in specific zones for removable dentures. Methods: Sixteen craniums were measured in 10 different zones. It was used an Electronic Digital Caliper 0-150 mm. Results: Consistently were applied F-test and Welch t-test for equality of variance and group's comparison mean, respectively. The spread of the data was described by calculating range and standard deviation. The estimated value of range was highest in the FI-A1P, followed by FI-AC and FI-A2P. The smallest amplitude was established in the TM-PP and SNA. The estimated value of standard deviation was 2,57/2,51 in FI-AC zone, 2,46/2,59 in FI-A1P zone and a few smaller 2,08/2,13 in FI-A2P zone. The lowest values were in TM-PP and SNA areas. Conclusion: Tuber maxillae and Spina nasalis anterior have stable dimensions. The areas of canine and premolars are varied, because the zone is tasked by chewing function.